2D HSQC Chemical Shifts of Impurities from Biomass Pretreatment. Issue 11 (19th March 2020) - Bryant, Nathan; G. Yoo, Chang; Pu, Yunqiao; Ragauskas, Arthur J.
Abstract: Two dimensional (2D) heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) is a powerful analytical method which can be used to elucidate the structure of biomass. During processing, biomass is typically subjected to some form of chemical treatment which can be performed with a variety of compounds. The presence of these compounds, even in trace amounts, has the potential to contaminate the sample and lead to misinterpretation of the HSQC spectra. Here we report the chemical shifts of 29 compounds commonly used in biomass processing which have the potential to contaminate the biomass samples and lead to the misinterpretation of peaks associated with biomass ( Populus trichocarpa ) pretreated via autohydrolysis. The identification of these chemical shifts could serve as a valuable tool in preventing errors in characterizing biomass via HSQC. Abstract : Compounds such as ionic liquids and deep eutectic solvents are gaining more attention as biomass pretreatment chemicals due to their "green" nature. Several of these compounds, as well as other organic solvents, have been analyzed via HSQC NMR for the potential interactions with biomass signals. The chemical shifts of these compounds combined with autohydrolysis pretreated biomass have been tabulated for their identification, with a notable shift change occuring with 1‐ethyl‐3‐methylimidazolium acetate.